Municipal solid waste incineration (MSWI) ashes for greener concrete - Glikson, Arnaud; López Menéndez, Sara (My University, 2019)
ABSTRACT Owing to the varying characteristics of municipal solid waste incineration (MSWI) ashes and the lack of harmonized standards and regulations, a substantial portion of MSWI ashes are simply used as landfilling cover at the present, which can be better utilized in the viewpoint of sustainability. This study aims at using and developing experimental methods to assess the reactivity of MSWI ashes under alkaline activation to evaluate their potential use as a binding agent. A new test, solution test, was developed in this work and performed on two kinds of MSWI ashes. The results were compared to an existing method, 𝑅􀬷 test. The solution test and 𝑅􀬷 test involve different activators, such as 𝐶𝑎(𝑂𝐻)􀬶, 𝑁𝑎𝑂𝐻 and 𝐾𝑂𝐻. The reactivity of the reacted mixtures was mainly determined by thermogravimetric analysis (TGA). The experiment results from 𝑅􀬷 test revealed that a concrete pore solution environment was not able to activate RISE BA (bottom ash) and STENA BA. Portlandite did not act as a good enough activator. The experiment results from the solution test showed that 𝑁𝑎𝑂𝐻 and 𝐾𝑂𝐻 activators added in order to reach a 𝑝𝐻 of 14, were able to activate RISE BA in addition to SLAG. However, STENA BA were still inert.
Keywords: Alkaline activation, bottom ashes, greener concrete, reactivity assessment, thermogravimetric analysis